PERLINDUNGAN HUKUM BAGI DOKTER DALAM PENGUNGKAPAN RAHASIA MEDIS UNTUK TUJUAN ASURANSI KESEHATAN: STUDI PERBANDINGAN INDONESIA DAN MALAYSIA - Yeni Vitrianingsih (Journal of Indonesian Comparative of Syari'ah Law, 2025)
This study aims to analyze and compare the legal protection mechanisms provided to physicians in Indonesia and Malaysia regarding the disclosure of medical confidentiality for insurance purposes. This study uses a normative juridical method with a statutory and comparative approach. Data were collected through a literature review of the Medical Practice Act, data confidentiality regulations, and Code of Ethics Council guidelines in both countries. The results show that Indonesia tends to provide conditional protection, where disclosure of confidentiality is mandatory based on the patient's written consent (informed consent) or statutory mandate, placing physicians at legal risk if such consent is not specific. Meanwhile, Malaysia, through the Personal Data Protection Act (PDPA) and related regulations, offers a more explicit protection framework for physicians if disclosures are made in accordance with hospital standard operating procedures (SOPs) and insurance policy terms, although this remains open to interpretation. In conclusion, regulatory harmonization in Indonesia is needed to clarify the boundaries and standard procedures for disclosing medical confidentiality to third parties (insurance companies), in order to provide greater certainty and protection for medical professionals.